The US Military HIV Natural History Study: Informing Military HIV Care and Policy for Over 30 Years. (28th November 2019) - Agan, Brian K; Ganesan, Anuradha; Byrne, Morgan; Deiss, Robert; Schofield, Christina; Maves, Ryan C; Okulicz, Jason; Chu, Xiuping; O'Bryan, Thomas; Lalani, Tahaniyat; Kronmann, Karl; Ferguson, Tomas; et al.
ABSTRACT: Introduction: In October 1985, 4 years after the initial descriptions of the acquired immunodeficiency syndrome (AIDS), the U.S. Department of Defense (DoD) began routine screening for human immunodeficiency virus (HIV) infection to prevent infected recruits from exposure to live virus vaccines, implemented routine active-duty force screening to ensure timely care and help protect the walking blood bank, and initiated the U.S. Military HIV Natural History Study (NHS) to develop epidemiologic, clinical, and basic science evidence to inform military HIV policy and establish a repository of data and specimens for future research. Here, we have reviewed accomplishments of the NHS over the past 30 years and sought to describe relevant trends among NHS subjects over this time, with emphasis on combination antiretroviral therapy (cART) use and non-AIDS comorbidities. Methods: Subjects who were prospectively enrolled in the NHS from 1986 through 2015 were included in this analysis. Time periods were classified by decade of study conduct, 1986–1995, 1996–2005, and 2006–2015, which also correlate approximately with pre-, early-, and late-combination ART (cART) eras. Analyses included descriptive statistics and comparisons among decades. We also evaluated mean community log10 HIV viral load (CVL) and CD4 counts for each year. Results: A total of 5, 758 subjects were enrolled between 1986 and 2015, of whom 92% were male with a median age of 28 years, and 45% were African-American, 42% Caucasian, and 13% Hispanic/other. The proportion of African-Americans remained stable over the decades (45%, 47%, and 42%, respectively), while the proportion of Hispanic/other increased (10%, 13%, and 24%, respectively). The CD4 count at HIV diagnosis has remained high (median 496 cells/uL), while the occurrence of AIDS-defining conditions (excluding low CD4 count) has decreased by decade (36.7%, 5.4%, and 2.9%, respectively). Following the introduction of effective cART in 1996, CVL declined through 2000 as use increased and then plateaued until guidelines changed. After 2004, cART use again increased and CVL declined further until 2012-15 when the vast majority of subjects achieved viral suppression. Non-AIDS comorbidities have remained common, with approximately half of subjects experiencing one or more new diagnoses overall and nearly half of subjects diagnosed between 2006 and 2015, in spite of their relatively young age, shorter median follow-up, and wide use of cART. Conclusions: The US Military HIV NHS has been critical to understanding the impact of HIV infection among active-duty service members and military beneficiaries, as well as producing insights that are broadly relevant. In addition, the rich repository of NHS data and specimens serves as a resource to investigators in the DoD, NIH, and academic community, markedly increasing scientific yield and identifying novel associations. Looking forward, the NHS remains relevant to understanding host factor correlates of virologic and immunologic control, biologic pathways of HIV pathogenesis, causes and consequences of residual inflammation in spite of effective cART, identifying predictors of and potential approaches to mitigation of excess non-AIDS comorbidities, and helping to understand the latent reservoir.